Toxicity Studies of Plant Extracts on Insects and Fish - Sukari, Mohd Aspollah; Rahmani, Mawardi; Manas, Abd Rahman; Takahashi, Sozho (1992)
Toxicity studies of several local plant extracts on insects and fish were carried out. The volatile fraction of some of plant extracts was isolated and the major components were characterized. The contact insecticidal activity and the toxicity test of the plant extract on fishes were studied.